Dampak Nilai Hardness berdasarkan Parameter Heat Input pada Proses Pengelasan GTAW untuk Material Superduplex Stainless Steel S32750 - Irawan, Benny Haddli; Saputra, Ihsan; Ardiyansyah, M (Politeknik Negeri Padang, 2024)
In this sophisticated era, the metal manufacturing process cannot be separated from welding process. Welding is a process of joining two metals using electrodes or filler metals which are commonly used in the world of fabrication and industry. Heat energy greatly affect the quality of the weld. Three parameter in heat energy is Ampere, Voltage and Heat input. The purpose of this study was to determine the effect of heat input to value of hardness on materials Superduplex Stainless Steel S32750 with GTAW process welding. The hardness of the material is very important to determine the resistance of a material. In the fabrication process threre are still material that have a hardness value that exceeds the standard value of the material manufacture. The welding process is carried out from root, hotpass, fill pass and capping with five variations of heat input to five the specimen of the test object, then do the hardness test with Vickers with a test kit portable UCI Sonodur 3. The hardness test carried out on weld metal, base metal and heat affected zone. From the analysis carried out with five variations of heat input and comparing the hardness values at each test location, a low heat input of 0.97 kJ/mm resulted in the highest average hardness value of 299.2 HV in the base metal area, the area exposed to heat (HAZ) of 265.9 HV, and the weld metal area of 229.5 HV. Based on this, it can be concluded that the hardness value in GTAW welding with low heat input has the highest hardness value compared to high heat input.